Dealing with manual handling - Safetycare Australia (Australia : Safetycare Australia, 2000)
Manual handling includes lifting, holding, pushing, pulling, shifting and lowering. In fact, any form of human exertion could be included - with or without the use of mechanical aids
Title from title screen
Keywords: Lifting and carrying; Industrial safety